E2F7 Transcriptionally Inhibits MicroRNA-199b Expression to Promote USP47, Thereby Enhancing Colon Cancer Tumor Stem Cell Activity and Promoting the Occurrence of Colon Cancer - Xiong Guo; Ling Liu; Qi Zhang; Weiming Yang; Yang Zhang (Frontiers in Oncology, 2021)
microRNAs (miRNAs) can modulate the expression level of genes in a post-transcription manner, which are closely related to growth and metastasis of colon cancer. Herein, we aimed to explore how miR-199b influences colon cancer and to characterize its underlying molecular mechanism associating with E2F transcription factor 7 (E2F7). Assays of RT-qPCR, Western blot, and immunohistochemistry were utilized to detect the expression of E2F7 in the tissue samples collected from 30 patients diagnosed with colon cancer. Flow analysis was utilized to detect the ratio of ALDH1+ and CD133+ colon cancer stem cells. The interaction between E2F7, miR-199b, USP47, and MAPK was identified by ChIP-Seq analysis, luciferase reporter, RNA pull-down, co-immunoprecipitation, as well as glutathione-S-transferase (GST) pull-down experiments. Based on the gain- and loss-of-function approaches, the cellular functions of colon cancer cells by the E2F7-regulated miR-199b/USP47/MAPK axis were assessed. It was identified that E2F7 are expressed highly in the collected colon cancer tissues. E2F7 silencing reduced the production of ALDH1+ and CD133+ colon cancer stem cells and antagonized the effects of 5-fluorouracil (5-FU) treatment. Besides, the silencing of E2F7 was observed to suppress the oxidative stress, proliferation, migration, as well as invasion of ALDH1+ cells in vitro and tumorigenesis of colon cancer cells in vivo. Our findings reveal the pro-oncogenic effect of E2F7 on colon cancer development, highlighting E2F7 as a novel target for therapeutic strategy for colon cancer.